2005
DOI: 10.1104/pp.105.071514
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Amine Substrate Specificity Domain of Pepper Tyramine and Serotonin N-Hydroxycinnamoyltransferases

Abstract: Pepper (Capsicum annuum) serotonin N-hydroxycinnamoyltransferase (SHT) catalyzes the synthesis of N-hydroxycinnamic acid amides of serotonin, including feruloylserotonin and p-coumaroylserotonin. To elucidate the domain or the key amino acid that determines the amine substrate specificity, we isolated a tyramine N-hydroxycinnamoyltransferase (THT) gene from pepper. Purified recombinant THT protein catalyzed the synthesis of N-hydroxycinnamic acid amides of tyramine, including feruloyltyramine and p-coumaroylty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…While BAHD proteins are responsible for the acylation of aliphatic and arylmonoamine acceptors, GNAT enzymes are active on arylamines (Bassard et al, 2010). Although they are from two distinct protein families that show low sequence identity, the BAHD N-acyltransferases, Os-THTs and Os-TBTs, identified in our study demonstrate that proteins from both families can act on aryldiamines (Tables 2 and 3; Jang et al, 2004;Kang et al, 2006). Comparing the specificity of the enzymes between the two families showed that whereas GNAT members are highly specific for tyramine, the BAHD enzymes may be regarded as bifunctional tryptamine/tyramine N-acyltransferases.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…While BAHD proteins are responsible for the acylation of aliphatic and arylmonoamine acceptors, GNAT enzymes are active on arylamines (Bassard et al, 2010). Although they are from two distinct protein families that show low sequence identity, the BAHD N-acyltransferases, Os-THTs and Os-TBTs, identified in our study demonstrate that proteins from both families can act on aryldiamines (Tables 2 and 3; Jang et al, 2004;Kang et al, 2006). Comparing the specificity of the enzymes between the two families showed that whereas GNAT members are highly specific for tyramine, the BAHD enzymes may be regarded as bifunctional tryptamine/tyramine N-acyltransferases.…”
Section: Discussionmentioning
confidence: 90%
“…Here, comparative sequence analysis with in vitro assays using mutant enzymes led to the identification of a RRRR motif that is sufficient to transform agmatine utilization ( Figures 9A and 9B), which is similar to the conserved arginine-rich motifs in RNA binding proteins (Lazinski et al, 1989;Zapp et al, 1991;Yuryev et al, 1996). This integrated approach has also been applied to identify key residues of enzymes involved in coumaroyl serotonin, terpene, and acylsucrose biosynthesis (Kang et al, 2006;Kang et al, 2014;Fan et al, 2016) and may be regarded as a general strategy in the structurefunction study of enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfactory yields were obtained in all cases. Piperic acid (2) was prepared by alkaline hydrolysis of piperine (1), by means of a previous procedure, 20) with modifications. Piperic acid amides (29 and 30) with aminoalkyl groups were synthesized by the condensation of the acid chloride (3) with the corresponding mono-Boc-diamines (26 and 28) followed by a deprotection step.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, the biosynthesis of tyramine and serotonin derivatives are catalyzed by the action of tyramine-and serotonin-N-hyroxycinnamoyltransferase, respectively. 1) Recent studies have reported the tyrosinase inhibitory effects of synthetic hydroxycinnamic acid amides, derived from coupling of caffeic acid and its derivatives with biogenic amines, such as tyramine, dopamine, and serotonin. [2][3][4][5] In addition, serotonin derivatives have a number of biological effects, such as α-glucosidase inhibition, 6) antioxidative activity, 7) and cyclooxygenase-2 (COX-2) inhibition.…”
mentioning
confidence: 99%